Increased gamma connectivity during working memory retention following traumatic brain injury. (23rd February 2017) - Bailey, Neil W.; Rogasch, Nigel C.; Hoy, Kate E.; Maller, Jerome J.; Segrave, Rebecca A.; Sullivan, Caley M.; Fitzgerald, Paul B.
ABSTRACT: Primary objective : Alterations to functional connectivity following a traumatic brain injury (TBI) may lead to impaired cognitive performance and major depressive disorder (MDD). In particular, functional gamma band connectivity is thought to reflect information binding important for working memory. The objective of this study was to determine whether altered functional gamma connectivity may be a factor in MDD following TBI (TBI-MDD). Research design : This study assessed individuals with TBI-MDD, as well as individuals with TBI alone and MDD alone using electroencephalographic recordings while participants performed a working memory task to assess differences in functional connectivity between these groups. Methods and procedures : Functional connectivity was compared using the debiased weighted phase lag index (wPLI). wPLI was measured from a group of healthy controls ( n = 31), participants with MDD ( n = 17), participants with TBI ( n = 20) and participants with TBI-MDD ( n = 15). Main outcomes and results : Contrary to the predictions, this study found both the groups with TBI and TBI-MDD showed higher gamma connectivity from posterior regions during WM retention. Conclusions : This may reflect dysfunctional functional connectivity in these groups, as a result of maladaptive neuroplastic reorganization.